Pelatihan Trauma Healing Berbasis Group Exercise Bagi Guru BK SMP di Kabupaten Kuningan - Nandang Rusmana; Anne Hafina; Nandang Budiman; Mutiara Aqilla Tasya; Muqaffi Muqaffi; Popy Mayasari Afendy; Khoirunnissa Khoirunnissa (Universitas Pendidikan Indonesia, 2023)
Indonesia is one of the countries prone to natural disasters. It is a country with a significant responsibility for educating and preparing students for success in the educational process. This study aims to provide insight to Guidance and Counseling (BK) teachers about the importance of understanding student conditions, provide BK teachers with basic concepts of PTSD and its treatment, and socialize and provide training on trauma healing. Methods. The training was conducted in junior high schools in Kuningan District. The outcomes of the meetings included: (1) conducting the community engagement activities online (July 26-27, 2023 via Zoom) and in-person (August 2, 2023); (2) the topics to be covered included the basic concept of traumatic stress disorder, counseling techniques for dealing with PTSD, post-trauma counseling programs, scientific article writing workshops, cognitive-behavioral therapy, eye movement desensitization and reprocessing, brief psychodynamic psychotherapy, exposure therapy, writing service implementation plans, and implementing group exercise-based post-traumatic counseling strategies. Results. The results indicated that 73% of participants found it easy to apply, while 26% found it somewhat difficult. Regarding individual counseling concepts, 93% found it easier to understand, while 7% found it quite challenging. Abstrak Indonesia merupakan salah satu negara yang rentan terhadap bencana alam. Negara ini memiliki tanggung jawab besar dalam mendidik dan mempersiapkan siswa untuk sukses dalam proses pendidikan. Penelitian ini bertujuan untuk memberikan wawasan kepada guru Bimbingan dan Konseling (BK) tentang pentingnya memahami kondisi siswa, memberikan guru BK dengan konsep dasar PTSD dan pengobatannya, serta mensosialisasikan dan memberikan pelatihan tentang penyembuhan trauma. Pelatihan ini dilakukan di sekolah menengah pertama di Kabupaten Kuningan. Hasil pertemuan mencakup: (1) melaksanakan kegiatan keterlibatan masyarakat secara online (26-27 Juli 2023 via Zoom) dan tatap muka (2 Agustus 2023); (2) topik yang akan dibahas meliputi konsep dasar gangguan stres trauma, teknik konseling untuk mengatasi PTSD, program konseling pasca trauma, lokakarya penulisan artikel ilmiah, cognitive-behavioral therapy, eye movement desensitization and reprocessing, brief psychodynamic psychotherapy, exposure therapy, penyusunan rencana pelayanan penulisan, dan implementasi strategi konseling pasca trauma berbasis latihan kelompok. Hasil penelitian menunjukkan bahwa 73% peserta merasa mudah untuk mengaplikasikannya, sementara 26% merasa agak sulit. Mengenai konsep konseling individu, 93% merasa lebih mudah untuk dipahami, sementara 7% merasa cukup sulit. Keywords: Trauma Healing; Group Exercise; PTSD; Guru BK